Ways of worldmaking - Goodman, Nelson (Sussex The Harvester Press, 1978)
In a way reminiscent of Einstein, Goodman leads us to the very edge of relativism, only then to step back and to suggest certain criteria of fairness and rightness. More so than any other commentator, he has provided a workable notion of the kinds of skills and capacities that are central for anyone who works in the arts." -- Howard Gardner, Harvard University